PENGARUH VARIASI DOSIS LARUTAN DAUN PEPAYA (Carica papaya L.)TERHADAP MORTALITAS HAMA KUTU DAUN(Aphis craccivora)PADA TANAMAN KACANG PANJANG(Vigna sinensis L.) SEBAGAI SUMBER BELAJAR BIOLOGI - Anak Agung Oka, Handi Setiawan (BIOEDUKASI (Jurnal Pendidikan Biologi), 2015)
Abstract: One of the obstacles that farmers faced is the presence of leaf pests. The effort to reduce the use of synthetic pesticides is necessary to look for the alternative ingredients derived from plants that have potential as plant pesticide. One of them is papaya plant. The purposes of this study are (1st) to know the whether there is effect of variant dose of papaya leaf solution toward mortality of leaf pests. (2nd) to know whether the dose of papaya leaf solution is the most appropriate for leaf pests mortality. (3rd) to arrange the biology learning source to senior high school students of tenth grades in even semester. This research was an experimental design and this research was completely randomizes design (RAL) by using five times repeats by using variant doses in the control treatment, 15gr/L, 20gr/L, 25gr/L, 30gr/L, 35gr/L. The data were analyzed by using non-parametric test one-way ANOVA. The results showed the percentage of the leaf pests from the lowest to the highest are control=0%, 15gr/L=64%, 30gr/L=68%, 20gr/L=76%, and 35gr/L=92%. From the result of discussion and conclusion that there was significant influence on the variant dose of papaya leaf solution toward mortality of leaf pests by testing the hypotheses that H0 was rejected and H1 was accepted. Because, X2count 18,25> X2 table 9,49 at and X2 count 18,25 > X2table 13,3 at Â on the chi-square table. Based on this result of the research and discussion, it can be conclude that (1st) there was significant influence on the administration of papaya leaf solution, toward mortality of leaf pests, it was gained the coefficient H=18,25 > chi-square value 9,49 at Î± level of 0,05 and 13,3 at Î± level 0,01. (2nd) at dose 35gr/L of papaya leaf solution was the best dose to mortality of the leaf pest. (3rd) the result can be used as a source of biology learning to senior high school students, tenth grades in even semester for the worksheet of Students Activity (LPKS) about the interaction of ecosystem of the pests and diseases in plants.